Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1177/17577438211052647
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ response to a challenge to change: A portrait of teacher resilience to a professional development program

Abstract: Teachers’ learning in keeping abreast of groundbreaking instructional techniques is crucial for their continuous development of which the ultimate goal is meaningful learning for students. However, research on the extent teachers respond to the demand to change especially on their assessment practice is limited. This study investigated teachers’ resilience on a new educational innovation on formative assessment which is group oriented. The study engaged a cohort of 100 high school teachers joining a profession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…As the role of teachers undergoes a transformation from traditional instruction to facilitation, there is an increasing expectation for educators to get involved in TPD. Confronted with this challenge, some teachers show resistance in this respect (Tamah & Wirjawan, 2022). Previous studies have revealed that teachers' difficulties in sustaining their commitment arise from intrapersonal, interpersonal, and system-related factors (Mansfield et al, 2016;Wang et al, 2022).…”
Section: Beginning Language Teachers' Perceived Difficultiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As the role of teachers undergoes a transformation from traditional instruction to facilitation, there is an increasing expectation for educators to get involved in TPD. Confronted with this challenge, some teachers show resistance in this respect (Tamah & Wirjawan, 2022). Previous studies have revealed that teachers' difficulties in sustaining their commitment arise from intrapersonal, interpersonal, and system-related factors (Mansfield et al, 2016;Wang et al, 2022).…”
Section: Beginning Language Teachers' Perceived Difficultiesmentioning
confidence: 99%
“…This can be achieved through cultivating balance in various aspects of a teacher's career. Teacher resilience stands out as a construct contributing to maintaining this balance (Hiver, 2018;Wang et al, 2021) and helps teachers actively engage in TPD programmes (Tamah & Wirjawan, 2022). According to Mansfield et al (2016), teacher resilience is a dynamic process involving the interaction of personal and environmental resources, aiding teachers in recovering from adversities and challenges in their classrooms.…”
Section: Language Teachers' Resiliencementioning
confidence: 99%
“…The limitations of this study are indicated by the absence of information related to the teaching experience of kindergarten teachers. Participants' teaching experience can affect the level of teacher resilience in making decisions to change (Tamah & Wirjawan, 2021).…”
Section: Conclusion and Suggestionsmentioning
confidence: 99%